The definition of pulmonary hypertension: history, practical implications and current controversies - Gabor Kovacs (European Respiratory Society, 2021)
The definition of pulmonary hypertension (PH) is based on a growing body of evidence and represents the result of ongoing discussions within the PH community over the past 50 years. In 2018, the most recent World Symposium on Pulmonary Hypertension introduced significant changes in the definition of PH by lowering the mean pulmonary arterial pressure threshold to >20 mmHg and (re)introducing the pulmonary vascular resistance ≥3 WU cut-off for all forms of pre-capillary PH. These changes and their potential clinical impact have been the subject of lively discussions in the community and some important questions and controversies have been identified. In this review we aim to present the development of the definition of PH over the past decades and discuss the main arguments that led to relevant modifications. In addition, we address the practical implications of the most recent changes and controversies that still exist. Educational aims To review the historical development of the definition of pulmonary hypertension. To discuss practical implications and current controversies of the currently recommended definitions of pulmonary hypertension and pulmonary arterial hypertension.